Profile and Work Immersion Performance of Accountancy, Business, and Man-agement (ABM) Students of Selected Implementing Schools in Subic District, Zambales, Philippines - Alcobendas, Jestoni R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Work immersion is a key subject under the Senior High School (SHS) curriculum that is conducted in different ways and time frame as needed by SHS learners. This study was conducted to find out the work immersion performance of the Grade 12 students at San Isidro High School and Subic National High School, Zambales, Philippines. The IV-DV model of this research involved the profile of the student respondents and their work immersion performances in the schools’ partner companies. This study utilized the descriptive method of research which adapted the DepEd Schools Division of Bulacan’s checklist for work immersion performance. Data revealed that student-trainees performed very satisfactorily on their work immersion showing good work ethics and personality suitable of a future employee in any company they want to apply in. Male and female ABM students have the same level in job skills which implied that the profile variables of the trainees have no influence on the work immersion performance. From the findings and conclusion of this study, the implementing schools may need to improve the academic performance of ABM students to reach an excellent level and may allow them to join trainings and seminars given to regular employees about improving work ethics and personality development.